ANALISIS PENGARUH FAKTOR FUNDAMENTAL DAN EVA TERHADAP HARGA SAHAM INDEKS LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2007-2011 - Terra Vira Ervinta; Zaroni . (Bina Ekonomi, 2013)
The objective of this research is to examine the effect of fundamental factors which are proxied by CR (Current Ratio), EPS (Earnings Per Share), and PER (Price to Earnings Ratio), as well EVA (Economic Value Added) toward stock price. Stock price is important to known by stockholders and corporate because it indicates the performance of corporate. The samples in this research are 11 companies that listed in Indeks LQ45 continually for period August 2006 until Januari 2012 and meet the criteria sampling of this study. The samples was determined based on purposive sampling method. Data that used in this research is secondary data, which is financial statements. The results of this research are (1) CR (Current Ratio) has not significant influence to stock price, (2) EPS (Earnings Per Share) has significant influence to stock price, (3) PER (Price to Earnings Ratio) has significant influence to stock price, (4) EVA (Economic Value Added) has not significant influence to stock price, and (5) CR (Current Ratio), EPS (Earnings Per Share), PER (Price to Earnings Ratio), and EVA (Economic Value Added) simultaneously have significant influence to stock price.Keywords: CR (Current Ratio), EPS (Earnings Per Share), PER (Price to Earnings Ratio), EVA (Economic Value Added), stock price